Stress Distribution and Mechanical Behaviour of Rock Mass Containing Two Openings Underground: Analytical and Numerical Studies - Lihai Tan; Gaofeng Wang; Ting Ren; Linming Dou; Xiaohan Yang; Shikang Song (Geofluids)
In this study, stress solution for rock mass containing two rectangular openings was calculated based on the Schwarz alternating method to investigate the stress distribution in rock mass around openings with different layouts. In addition, large-scale numerical models were further established for the two-opening system by means of the PFC-FLAC coupling method, in which the stress evolution, failure patterns, and acoustic emission (AE) events were presented. With the combination of analytical and numerical solutions, the interaction mechanism between two openings under different layouts was discussed from the perspective of stress and failure. The result shows that the confining stress within a certain range contributes to relieving tensile stress concentration around openings. The stress condition within the connecting area and coalescence pattern between two adjacent openings is dominated by their layout. Compared with small-size rock specimens in laboratory tests, the failure patterns around openings show a better agreement with the stress concentration characteristics determined by analytical stress solutions.